Attenuation of Oxidative Injury With Targeted Expression of NADPH Oxidase 2 Short Hairpin RNA Prevents Onset and Maintenance of Electrical Remodeling in the Canine Atrium: A Novel Gene Therapy Approach to Atrial Fibrillation. Issue 13 (29th September 2020) - Yoo, Shin; Pfenniger, Anna; Hoffman, Jacob; Zhang, Wenwei; Ng, Jason; Burrell, Amy; Johnson, David A.; Gussak, Georg; Waugh, Trent; Bull, Suzanne; Benefield, Brandon; Knight, Bradley P.; et al.
Abstract : Background: Atrial fibrillation (AF) is the most common heart rhythm disorder in adults and a major cause of stroke. Unfortunately, current treatments of AF are suboptimal because they are not targeted to the molecular mechanisms underlying AF. Using a highly novel gene therapy approach in a canine, rapid atrial pacing model of AF, we demonstrate that NADPH oxidase 2 (NOX2) generated oxidative injury causes upregulation of a constitutively active form of acetylcholine-dependent K + current ( I KACh ), called I KH ; this is an important mechanism underlying not only the genesis, but also the perpetuation of electric remodeling in the intact, fibrillating atrium. Methods: To understand the mechanism by which oxidative injury promotes the genesis and maintenance of AF, we performed targeted injection of NOX2 short hairpin RNA (followed by electroporation to facilitate gene delivery) in atria of healthy dogs followed by rapid atrial pacing. We used in vivo high-density electric mapping, isolation of atrial myocytes, whole-cell patch clamping, in vitro tachypacing of atrial myocytes, lucigenin chemiluminescence assay, immunoblotting, real-time polymerase chain reaction, immunohistochemistry, and Masson trichrome staining. Results: First, we demonstrate that generation of oxidative injury in atrial myocytes is a frequency-dependent process, with rapid pacing in canine atrial myocytes inducing oxidative injury through the induction of NOX2 and the generation of mitochondrial reactive oxygen species. We show that oxidative injury likely contributes to electric remodeling in AF by upregulating I KACh by a mechanism involving frequency-dependent activation of PKCε (protein kinase C epsilon). The time to onset of nonsustained AF increased by >5-fold in NOX2 short hairpin RNA–treated dogs. Furthermore, animals treated with NOX2 short hairpin RNA did not develop sustained AF for up to 12 weeks. The electrophysiological mechanism underlying AF prevention was prolongation of atrial effective refractory periods, at least in part attributable to the attenuation of I KACh . Attenuated membrane translocation of PKCε appeared to be a likely molecular mechanism underlying this beneficial electrophysiological remodeling. Conclusions: NOX2 oxidative injury (1) underlies the onset, and the maintenance of electric remodeling in AF, as well, and (2) can be successfully prevented with a novel, gene-based approach. Future optimization of this approach may lead to a novel, mechanism-guided therapy for AF. Abstract : Supplemental Digital Content is available in the text.